Impact of urbanization and economic growth on environmental quality in western africa: Do manufacturing activities and renewable energy matter? - Radoine, Hassan; Bajja, Salwa; Chenal, Jerome; Ahmed, Zahoor (Frontiers in Environmental Science, 2022)
The countries in Western Africa have the greatest potential for renewable energy generation in the world and are likely to be vulnerable to the adverse effects of climate change. Unfortunately, only a few of them have tapped into this potential, as non-renewable energy still dominates the total energy mix of these countries. The present study explores the effect of economic growth, manufacturing value added, urbanization, financial development, foreign direct investment and renewable energy consumption on the environmental quality in West African countries by using a sample of some selected countries over the period 1991–2018. This study is analyzed by adopting the method of Driscoll-Kraay (DK) panel regression. The panel result suggests that manufacturing value-added, urbanization, financial development and foreign direct investment increase environmental degradation. In addition, the findings of this study reveal that economic growth and renewable energy consumption contribute, significantly, to environmental quality. Bidirectional causality exists between economic growth and CO2 emissions and between urbanization and environmental degradation. Accordingly, in order to decrease this damage in these countries, it is imperative to embrace and promote the consumption of clean energy sources, which will contribute more to the promotion and adoption of renewables in this strategic region.